2007
DOI: 10.1007/s10620-007-9873-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biodegradable Stents for Benign Esophageal Strictures Following Endoscopic Submucosal Dissection

Abstract: The application of metallic stents for benign stenosis is limited due to long-term complications. We report here the results of the implantation of a novel biodegradable poly-L-lactic acid (PLLA) esophageal stent in two patients with benign esophageal stenosis after endoscopic submucosal dissection (ESD). Case 1 was a 64-year-old man who received ESD for an early squamous esophageal cancer in the middle esophagus. The mucosal defect was seven-eighths of the circumference, and the distal margin of the resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 20 publications
(24 reference statements)
0
85
0
2
Order By: Relevance
“…There are other ways to treat esophageal stenosis, such as temporary stent insertion and local corticosteroid injection [10,19]. Prior studies suggest the usefulness of intralesional steroid injection into benign esophageal strictures for augmentation of the effects of endoscopic dilatation [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other ways to treat esophageal stenosis, such as temporary stent insertion and local corticosteroid injection [10,19]. Prior studies suggest the usefulness of intralesional steroid injection into benign esophageal strictures for augmentation of the effects of endoscopic dilatation [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that triamcinolone can prevent the cross-linking of collagen that results in scar stricture [20]. More recently, there have been several preclinical or preliminary studies to overcome esophageal strictures using new technologies, such as biodegradable stents [19] or autologous oral mucosal sheets [21]. However, until these are available in the clinical setting, our experience with systemic prednisolone administration for complete circular ESD may offer an alternative to decrease the risk of benign esophageal strictures and reduce the number of EBD sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, oral mucosal epithelial cell sheet transplantation applying regenerative medicine technology (18,19), and the usefulness of biodegradable stents (20) have been reported and new clinical applications are expected. In cell sheet transplantation, expensive medical expenses are required to prepare cell sheets, and there are problems to be solved such as it taking no less than 2 weeks at Tokyo Women's Medical University Hospital.…”
Section: Risk and Prevention Of Post-procedural Stenosismentioning
confidence: 99%
“…Saito et al [52] reported two cases in whom biodegradable stents for post-ESD esophageal strictures were successfully placed. In both lesions, the mucosal defect had extended to seven-eighths of the circumference.…”
Section: Management Of Esophageal Stricture After Esdmentioning
confidence: 99%